Who are we online? The interplay between online identity formation and Christian marriages - Ferreira, Chantal (HTS teologiese studies, 2021)
Digital technologies have become an integrated part of everyday life, and this development has not left relationships untouched. A need exists for theological reflection on the interaction between the dynamic contexts of the digital age and Christian marital relationships. The relational implications of the digital age are quite vast; therefore the focus of the article will be limited to online identity formation as a particular challenge of the digital age. Employing the method of a literature study within the scientific field of practical theology, this article explores the interplay between online identity formation and Christian marriage. It suggests that online identity formation exists around a reciprocal interaction with two prominent qualities of Christian marriages: The expansion of the self and one-ness. When considering the interplay between online identity formation and Christian marriage, awareness can be created regarding the marital implications of spouses’ online engagements, which may enhance contextual pastoral care with a relational focus within the digital age.Contribution: The article contributes to practical theological reflection on challenges posed to Christian marriages by the digital age. It is aimed at stimulating pastoral thinking regarding online identity formation and its adverse effects on so-called one-ness in Christian marriages that can enhance pastoral care with a view on the flourishing of couples in the digital age.